Differential Effects of Functioning on the Career Development of Individuals with Disabilities. (April 2023) - Brehmer, Chelsea E.; Strauser, David R.; Shen, Sa; Phillips, Brian N.; Kosciulek, John F.; Austin, Bryan S.
Individuals with disabilities experience disproportionate rates of unemployment and underemployment when compared to individuals without disabilities. Furthermore, health functioning impacts career development and employment across multiple life contexts. To build on what is known regarding the relationships between functioning and career development, this study focuses on delineating how varying aspects of functioning differentially impact specific areas of career development. Based on data collected from 674 individuals with disabilities in the United States this study investigated the relationship between individual health functioning and the following three core components of career development: vocational identity, work personality, and work adjustment. Findings illuminate important differences across dimensions of functioning that impact career development. Results suggest that a multidimensional approach to career development would be most efficacious in supporting the functioning of individuals with disabilities.